CHARACTERISTICS OF THE TREATMENT PROCESS IN PATIENTS WITH FRACTURES OF THE SHOULDER BONE ON A BACKGROUND OF COVID-19 - Tanasiienko, P.V.; Guriev, S.O.; Skobenko, E.O. (World of Medicine and Biology, 2024)
The purpose of the study was to analyze the distribution of patients with shoulder fractures during the COVID-19 epidemic and to determine changes in their treatment approaches. To carry out the study, we retrospectively analyzed the treatment of 289 trauma patients who underwent inpatient treatment at the Kyiv City Clinical Emergency Medical Hospital from 2019 to 2021. During the epidemic of COVID-19, the number of cases of damage to the girdle of the upper limb significantly decreased, which included all localizations except damage to the distal part of the forearm, where an increase in the number was found during this period. Epidemic restrictions and screening mechanisms for patients with upper extremity fractures during COVID-19 have changed approaches to the treatment of patients with upper extremity fractures towards a wider use of conservative treatment methods, which applied to all locations, except for patients with fractures of the distal humerus, where the structure of treatment showed almost the same tendency in comparison with the treatment of similar patients in the pre-epidemic period.